Comparison on Two-Dimensional Ultrasound to Three-Dimensional Placenta Image using Segmentation Techniques - Manoharan, J. James (International Journal of Computer Sciences and Engineering, 2025)
Ultrasound Placenta image are usually low in resolution which may lead to loss of characteristics features of the image. Discarded at birth, the placenta is a highly complex and fascinating organ. During the course of a pregnancy, it acts as the lungs, gut, kidneys, and liver of the fetus. Ultrasound is a diagnostic technique which has many purposes though it is typically used by a Gynecologist to check the fetus in the mother's womb during pregnancy. Image Segmentation is very important in many medical reputation applications. This survey aims at providing an insight about different 2-Dimensional and 3-Dimensional Placenta image segmentation techniques and to help better understanding to the people who are new in this field. This comparative study summarizes the benefits and limitations of various segmentation techniques